Clinical and molecular characteristics associated with Vitamin C deficiency in myeloid malignancies; real world data from a prospective cohort. (February 2023) - Premnath, Naveen; Chung, Stephen S.; Weinberg, Olga K.; Ikpefan, Ruth; Pandey, Mohak; Kaur, Gurbakhash; Geethakumari, Praveen Ramakrishnan; Afrough, Aimaz; Awan, Farrukh T.; Anderson, Larry D.; Vusirikala, Madhuri; Collins, Robert H.; et al.
Abstract: Vitamin C is an essential vitamin that acts as a co-factor for many enzymes involved in epigenetic regulation in humans. Low vitamin C levels in hematopoietic stem cells (HSC) promote self-renewal and vitamin C supplementation retards leukaemogenesis in vitamin C-deficient mouse models. Studies on vitamin C levels in patients with myeloid malignancies are limited. We thus conducted a retrospective analysis on a prospective cohort of patients with myeloid malignancies on whom plasma vitamin C levels were measured serially at diagnosis and during treatment. Baseline characteristics including hematological indices, cytogenetics, and molecular mutations are described in this cohort. Among 64 patients included in our study, 11 patients (17%) had low vitamin C levels. We noted a younger age at diagnosis for patients with myeloid malignancies who had low plasma vitamin C levels. Patients with low plasma vitamin C levels were more likely to have acute myeloid leukemia compared to other myeloid malignancies. Low vitamin C levels were associated with ASXL1 mutations. Our study calls for further multi-institutional studies to understand the relevance of low plasma vitamin C level in myeloid neoplasms, the role of vitamin C deficiency in leukemogenesis, and the potential benefit of vitamin C supplementation.